The writing as a word: País íntim, by Maria Barbal - Ribes, Sandrine (Revista de Filología Románica, 2012)
The work of Maria Barbal stands in particular within the landscape of literature written by women in Catalan. Her book País íntim (2005) illustrates the evolution of women in contemporary Catalan novel written in first person. The author develops the topic of building a personal identity, more specifically a woman’s identity that is built in the framework of a complex mother-daughter relationship. I will try, in this article, analyzing the narrative procedures which are used by the author who makes her writing a word in time and how the aesthetic project of constructing an imaginary dialogue becomes an ethical intention.